Design and analysis of electric Go-Kart. (2021) - Krishnamoorthi, Sangeetha; Prabhu, L.; Shadan, MD; Raj, Harsh; Akram, Nadeem
Abstract: The Go Kart vehicle is made without a suspension and differential and used by the people who are interested in racing sports like Formula 1 or Formula E etc. Normally the Go Kart is powered by IC engines and in this paper we have designed and analyzed the go Kart by using electric motor. The detailed design calculations and analysis of the Electric Go kart is done with utmost care and the main aim is to obtain a light weight and high performing vehicle. From the different materials selected AISI 1018 was found to the better material for making the chassis frame. Then the 3D solid modeling was done in Solidworks 2020 CAD software and the Analysis part was done in the Ansys 2019 R2. By analyzing all the front, side and rear impact of the chassis the deformation, equivalent stress were found out. The steering system was provided with Ackerman angle while the caster angle and king pin inclination was about 12° and 7°. The analysis was carried out with different iterations and finally the optimum design of each part of the Go kart was done so as to obtain the optimum result.